PENGARUH GAYA KEPEMIMPINAN KEPALA MADRASAH TERHADAP KINERJA PENDIDIDIK DAN KEPENDIDIKAN DI MADRASAH IBTIDAIYAH (MI) AL HUDA MAGUWO, SLEMAN. - Noorrela Ariyunita (STAI Ma'had Aly Al-Hikam Malang, 2019)
This research is a type of field research analyzing by taking the background of MI Al Huda, Maguwo, Sleman as a place of the research. The subjects of this study are principals, teachers, and students of MI Al Huda, Maguwo, Sleman. The object of this research is the educational leadership influence of the madrasa principals on the performance of educators and educational personnel. Data collection is done by conducting observations, interviews, and documentation. This research uses a phenomenological approach. The results of this research indicate the influence of the principal leadership on the performance of educators and educational personnel in MI Al Huda, Maguwo, Sleman, DIY. A conclusion of this research are (1) The principal always prioritizes deliberation and respect the opinions of subordinates before making decisions or policies in Madrasa. (2) The principal of the Madrasah gives freedom to educators and educational personnel to be creative and innovative in carrying out their duties. (3) The principal always tries to be a father figure for students by trying to be close and familiar with students. (4) The principal always controls every activity. (5) The principal always involves all school members and the local community to reach school goals.